A numerical analysis of air entrapment during droplet impact on an immiscible liquid film. (March 2020) - Yeganehdoust, Firoozeh; Attarzadeh, Reza; Karimfazli, Ida; Dolatabadi, Ali
Highlights: Comprehensive numerical study of droplet impact and bouncing from an immiscible liquid film surface using VOF method. Characterizing the liquid film and the air cushion hydrodynamics for various Weber numbers and film thicknesses. Droplet detachment due to the combined effect of air entrapment and the liquid film interface deformation. Abstract: The air entrapment during droplet impingement is responsible for spontaneous droplet bouncing on an arbitrary solid surface at low Weber numbers. However, for the impact on liquid film surfaces, the outcome would significantly change, making it more favorable for the fabrication of non-wetting lubricant impregnated surfaces (LIS/SLIPS). In this paper, we describe a problem associated with the impact on a liquid surface using a three-phase flow model that captures the details of the gas layer thickness and dynamics of fluid motions. The numerical model was based on the finite volume solution coupled with the volume of fluid method to track the phases. The model was validated with the analytical solution. Consequently, the numerical tool was utilized to investigate the thickness of the entrapped air during the impact process while the behavior of droplet and the immiscible liquid film was quantitatively measured. The morphology of the interfacial gas layer was analyzed for key parameters including impact velocity and film thickness. It was observed that the presence of liquid film can reduce the probability of rupturing the gas layer. The results for the profile of liquid film during droplet impact illustrated that the effect of film thickness can considerably influence the bouncing behavior.